Racismo algorítmico : o enviesamento tecnológico e o impacto aos direitos fundamentais no Brasil - Lima, Bruna Dias Fernandes (2022)
The implementation of algorithmic systems that are emulated by human instructions, performing the compilation of data that adapt simultaneously, represents significant risks for vulnerable groups in the information society. The present work aimed to analyze algorithmic racism as a consequence of the structural aspect inserted in current technological applications, mainly in facial recognition, which demonstrate discriminatory biases through the reproduction of patterns with negative traits, embedded in the algorithms guidelines and, consequently, minorities are affected with the violation of fundamental human rights in the use of technology to identify people. The problem focuses on the manifestation of discriminatory practices in technologies, based on sensitive personal data and what needs to be considered in this use, establishing relationships with the existing legal framework to combat algorithmic racism. In the course of the work, the context of algorithmic structural racism was addressed, passing through the concept of prejudice and discrimination, as well as that of racism and its confrontation in the axis of fundamental human rights. Algorithmic racism in the information society, understood as a socio-technical phenomenon, is emphasized to address the subsequent racial discriminatory practices arising from the digital environment, including in relation to the regulation of Artificial Intelligence, which promotes the main processes of stigmatization. In addition, it encourages reflection on the conception of the legal position beyond the protective effects with the perspective of an anti-racism in technology, centralizing the hypothesis of the possibility of providing an Artificial Intelligence that is ethical and inclusive having the right as a foundation, but also a technology society based on diversity. In order to do so, we used the technique of bibliographic research linked to the method of legal-sociological methodological approach, in view of the critical analysis of Law as a dependent variable of social demands in accordance with the process of constitutionalization of rights and citizenship that submits the effectiveness of current regulation.